2020
DOI: 10.14715/cmb/2020.66.7.26
|View full text |Cite
|
Sign up to set email alerts
|

Raddeanin A suppresses lung cancer cell proliferation via induction of apoptosis and increased production of ROS

Abstract: At present, in vitro cell experiments have confirmed that RaddeaninA can effectively inhibit the proliferation of some tumor cells, but the effect of RaddeaninA on lung cancer cells has not been observed. Therefore, this study explored its effect on lung cancer cells and its mechanism of action. Human lung cancer cell lines were treated with serum-free medium and varied concentrations of Raddeanin A. Cell proliferation and apoptosis were determined using MTT, and flow cytometric assays, respectively. The intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They are involved in low concentrations in cell viability and proliferation and conversely in high concentrations in cell killing. Research has shown that various compounds have been able to reduce proliferation and survival in cancer cells by increasing the level of ROS (Gill et al, 2016;Yang et al, 2019;Jin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in low concentrations in cell viability and proliferation and conversely in high concentrations in cell killing. Research has shown that various compounds have been able to reduce proliferation and survival in cancer cells by increasing the level of ROS (Gill et al, 2016;Yang et al, 2019;Jin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine monophosphate-activated protein kinase (AMPK) is an energy signal-sensing protein ubiquitously expressed in cells of body tissues where it participates in the maintenance of cell homeostasis. On activation by sugar, hypoxemia or oxidative stress, AMPK activates downstream signaling pathways, thereby keeping intracellular energy level constant, while maintaining normal cell division cycle [17][18][19].…”
Section: Discussionmentioning
confidence: 99%